THE FIRST RECORD OF MITES OF THE GENUS NEHARPYRHYNCHUS (ACARIFORMES: HARPIRHYNCHIDAE) FROM BIRDS IN PARAGUAY - Literák, Ivan (2014)
Three mite species of the genus Neharpyrhynchus (Acariformes: Harpirhynchidae) were recorded on wild birds represented by new hosts in Paraguay: Neharpyrhynchus trochilinus ex Chlorostilbon lucidus (=aureoventris) (Apodiformes: Trochilidae), Neharpyrhynchus tangara ex Paroaria capitata and P. coronata (Passeriformes: Thraupidae), and Neharpyrhynchus aff. spinus ex Setophaga (=Parula) pitiayumi (Passeriformes: Parulidae). Records from C. aureoventris, P. capitata, P. coronata and P. pitiayumi represent new host-parasite associations. Mites of this genus were recorded in Paraguay for the first time.